Islamic Philosophy and the Development of Islamic Thought - Fahrul Anam (International Journal of Nusantara Islam, 2019)
Islamic philosophy is the result of Islamic thought. This Islamic thought is the fruit of the encouragement of the teachings of the Qur'an and Hadith. Islamic thinking is a unique thought, different from the others. Because Islamic thought originates from revelation or relies on the explanation of revelation, while other thoughts that develop among humans, both in the form of non-celestial religions, political and economic ideologies, and social theories simply emerge from the genius of thinking human who gave birth to it. This article tries to discuss it.